STUDY OF THE EFFECT OF HYPOTHERMIC CONSERVATION ON THE INTRACELLULAR SODIUM CONCENTRATION IN THE ENDOTHELIUM OF CORNEAL TRANSPLANTS - G. S. Baturina; I. G. Palchikova; A. A. Konev; E. S. Smirnov; L. E. Katkova; E. I. Solenov; I. А. Iskakov (Вавиловский журнал генетики и селекции)
Endothelial keratoplasty has become the treatment of choice for corneal endothelial dysfunction. Advancements in the surgical treatment of corneal endothelial diseases depend on progress in graft conservation and its related advantages in assessing the suitability of grafts for transplantation. Transport of water and ions by cornea endothelium is important for the optic properties of cornea. In this work, we study the intracellular sodium concentration in cornea endothelial cells in samples of pig cornea that underwent hypothermic conservation for 1 and 10 days and endothelial cells of human cornea grafts after 10-day conservation. The concentration of intracellular sodium in preparations of endothelial cells was assayed using fluorescent dye SodiumGreen. The fluorescent images were analyzed with the custom-made computer program CytoDynamics. An increased level of intracellular sodium was shown in the endothelium after 10-day conservation in comparison with one-day conservation (pig samples). Sodium permeability of pig endothelial cell plasma membranes significantly decreased in these samples. Assessment of intracellular sodium in human cornea endothelium showed a higher level – as was in analogues pig samples of the corneal endothelium. The assay of the intracellular sodium balance concentration established in endothelial cells after hypothermic conservation in mediums L-15 and Optisol-GS showed a significant advantage of specialized me dium Optisol-GS. The balanced intracellular concentration after 10 days of hypothermic conservation was significantly lower in cells incubated at 4 °C in Optisol-GS (L-15, 128 ± 14,  n = 15; Optisol-GS, 108 ± 14, n = 11; mM, p < 0.001). Intracellular sodium concentration could be a useful parameter for assessing cornea endothelium cell viability.